Probiotics – which, whom, when? - Czerwionka-Szaflarska, Mieczysława; Romańczuk, Bartosz (Przewodnik Lekarza/Guide for GPs, 2008)
Probiotics are live microorganisms which when administered in adequate amounts confer a health benefit on a host. Lactic acid bacteria (Lactobacillus and Bifidobacterium) are the most common type of microbes used. The most widely used probiotic bacteria is Lactobacillus GG (Lactobacillus rhamnosus GG) which activity was particularly examined. There are different sources of probiotics: medicines, diet supplements and fermental products (yoghurts and kefirs). In this publication we present results of different clinical studies concerning the use of probiotics in prevention and treatment of the chosen paediatric diseases, especially digestive tract pathologies.